1990
DOI: 10.1136/jnnp.53.8.633
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin treatment of cranial-cervical dystonia, spasmodic dysphonia, other focal dystonias and hemifacial spasm.

Abstract: In the past five years, 477

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0
14

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(166 citation statements)
references
References 19 publications
5
147
0
14
Order By: Relevance
“…9,11 This duration of action was the same as that of BTx in its other indications, 6,7 the transitoriness of the e ect being due to synaptic regrowth after injection. 7 However, in two patients in our series, the clinical e ect lasted beyond the usual duration of action of BTx, which might signify a more durable modi®cation of the re¯ex status and urethral behaviour.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…9,11 This duration of action was the same as that of BTx in its other indications, 6,7 the transitoriness of the e ect being due to synaptic regrowth after injection. 7 However, in two patients in our series, the clinical e ect lasted beyond the usual duration of action of BTx, which might signify a more durable modi®cation of the re¯ex status and urethral behaviour.…”
Section: Discussionmentioning
confidence: 63%
“…6,7 It was ®rst evaluated as a treatment for DSD by Dykstra et al 8,9 in 16 patients, then by Schurch et al 10,11 in 24 patients. These studies showed that BTx relaxes the external urethral sphincter (EUS) and reduces DSD in approximately 80% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…A duração média do efeito foi de 2,9 meses (em torno de 12 semanas). Jankovic e col. 10 , obtiveram melhora em 94% dos pacientes, com média de duração de 15,7 semanas. Três dos nossos pacientes não apresentaram qualquer melhora, sendo que 2 em duas sessões.…”
Section: Discussionunclassified
“…Способность БТ влиять на аффе-рентные проводящие пути используется при лечении мигрени и болевых синдромов. Парадоксально, что реги-страция новых показаний к применению БТ происходила к моменту, когда в мире уже накапливался и обобщался достаточно большой независимый опыт ботулинотерапии по данному показанию [12,13]. И сейчас медицинское сообщество продолжает поиск новых показаний к при-менению БТ как на уровне международных контролируе-мых клинических протоколов, так и на уровне независи-мых пилотных исследований.…”
Section: клиническое применениеunclassified